Многокомпонентная защитная система остановки грузоподъемных кранов - Ісьєміні, Ілля Ігорович; Лях, Б. Г.; Сычев, Ю. И. (Eastern-European Journal of Enterprise Technologies, 2009)
In the article the ways of exception crane accidents by reliability growth of the crane protective system in the ends of runway are considered. Necessity and reasonability of generation of multielement crane protective system is shown and the plan it’s realization is given